Politik Hukum Pembangunan Kemaritiman Dalam Batasan Wilayah Perairan di Indonesia - Rahmat Saputra; Apriyanti Widiansyah (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2023)
The importance of maritime development legal politics is because the Indonesian nation until now has not had a national policy on the development of an integrated archipelagic state, weak understanding and awareness of Indonesia as an archipelagic state, has not set the boundaries of territorial waters even though the territorial waters, weak defense and state resilience from the seaside. Based on these problems, efforts to protect and ensure state security by sea are absolute. How is the legal politics of maritime development within the boundaries of territorial waters in Indonesia and how the enforcement of maritime law in Indonesian maritime waters is related to the country's maritime security? This research uses empirical juridical research methods, through tracing and reviewing secondary data, in the form of laws and regulations, academic manuscripts, policy recommendations, and scientific works of experts in the field of maritime development. The results of the discussion of the internationally recognized politics of maritime development law are very important, as a rule that can be used as a reference, especially by countries that have ratified it in determining maritime policy. The government has set various development policies and development of the maritime sector and is still weak in consistency and priority of implementation of these programs. Law enforcement in the maritime sector of Indonesia related to state maritime security is indispensable for the implementation of state maritime security in inland waters, archipelagic waters, Indonesian territorial seas, sea lanes, straits for international shipping of the Indonesian continental shelf, EEZ, and additional zones due to various forms of threats and threats to the Indonesian sea which has abundant natural resource potential and geographical position and strategic geopolitics.